Substituted N-(Pyrazin-2-yl)benzenesulfonamides; Synthesis, Anti-Infective Evaluation, Cytotoxicity, and In Silico Studies - Bouz, Ghada; Juhás, Martin; Pausas Otero, Lluis; Paredes de la Red, Cristina; Janďourek, Ondřej; Konečná, Klára; Paterová, Pavla; Kubíček, Vladimír; Janoušek, Jiří; Doležal, Martin; Zitko, Jan (Molecules (Basel, Switzerland), 2019)
We prepared a series of substituted N-(pyrazin-2-yl)benzenesulfonamides as an attempt to investigate the effect of different linkers connecting pyrazine to benzene cores on antimicrobial activity when compared to our previous compounds of amide or retro-amide linker type. Only two compounds, 4-amino-N-(pyrazin-2-yl)benzenesulfonamide (MIC = 6.25 μg/mL, 25 μM) and 4-amino-N-(6-chloropyrazin-2-yl)benzenesulfonamide (MIC = 6.25 μg/mL, 22 μM) exerted good antitubercular activity against M. tuberculosis H37Rv. However, they were excluded from the comparison as they-unlike the other compounds-possessed the pharmacophore for the inhibition of folate pathway, which was proven by docking studies. We performed target fishing, where we identified matrix metalloproteinase-8 as a promising target for our title compounds that is worth future exploration.
Keywords: Chemical Phenomena; Models, Molecular; antiinfekční látky; Chemistry Techniques, Synthetic; Mycobacterium tuberculosis; anti-infectives; Anti-Infective Agents; pyrazinamide; target fishing; chemické jevy; Microbial Sensitivity Tests; sulfonamidy; sulfonamide; Antitubercular Agents; molekulární modely; Sulfonamides; vztahy mezi strukturou a aktivitou; techniky syntetické chemie; benzensulfonamidy; molekulární struktura; Benzenesulfonamides; mikrobiální testy citlivosti; antituberkulotika; Structure-Activity Relationship; Molecular Structure